1976
DOI: 10.1515/bchm2.1976.357.1.499
|View full text |Cite
|
Sign up to set email alerts
|

Initeractions of Glycosaminoglycans with DNA and RNA Synthesizing Enzymes in vitro

Abstract: The sulfated glycosaminoglycans chondroitin 4-sulfate, chondroitin 6-sulfate, keratan sulfate, dermatan sulfate, heparin, and a glycosaminoglycan polysulfate are competitive inhibitors of the DNA-dependent DNA polymerase, the DNA-dependent RNA polymerase and the RNA-dependent DNA polymerase (reverse transcriptase). The unsulfated glycosaminoglycans chondroitin and hyaluronate are without any influence on the synthesis of DNA and RNA.The strongest inhibitor is a glycosaminoglycan polysulfate with four sulfate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Heparin is taken into cells, such as fibroblasts, 18 by a process of cell-surface binding 19,20 followed by internalization and metabolism of the glycosaminoglycan into oligosaccharides. 21,22 Internalized heparin or its metabolites could change cellular metabolism, 23 resulting in an alteration in the production of extracellular matrix proteins. Alteration of cellular metabolism could also cause in a change in enzyme systems that affect cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin is taken into cells, such as fibroblasts, 18 by a process of cell-surface binding 19,20 followed by internalization and metabolism of the glycosaminoglycan into oligosaccharides. 21,22 Internalized heparin or its metabolites could change cellular metabolism, 23 resulting in an alteration in the production of extracellular matrix proteins. Alteration of cellular metabolism could also cause in a change in enzyme systems that affect cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where marine organisms were able to inhibit this enzyme, it was always pure compounds which were hydrophilic in nature, suggesting that for activity against this enzyme, more aqueous extracts should be prepared [33]. On the other hand most of the extracts inhibited HIV-1 PR enzyme in the direct assays.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth patent is for the use of carrageenan and other sulfated polysaccharides for the treatment of diseases (including AIDS) caused by retroviral infection [42]. In another study on the hydrophilic metabolites (sulfated oligo- or poly-saccharide compounds) from red algae, retroviral replication was suppressed and viral reverse transcriptase inhibited [33]. …”
Section: Resultsmentioning
confidence: 99%
“…This later was verified by colleagues in England and Japan . Studies as early as that of Solomon et al (1966) and other work in the 1970s (Schaffrath et al, 1976) showed that sulfated oligo-or poly-saccharide compounds supressed retroviral replication and inhibited viral reverse transcriptases . Tests run in Japan, using a reversetranscriptase inhibition assay, showed that nearly all of the 39 species we had collected contained an inhibitory substance (Table 1) .…”
Section: Red Algal Extracts and Carrageenan As Antiviral Agentsmentioning
confidence: 93%